2017
DOI: 10.1371/journal.pone.0185759
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity structure of cortical calcium dynamics in anesthetized and awake mice

Abstract: The interplay between hemodynamic-based markers of cortical activity (e.g. fMRI and optical intrinsic signal imaging), which are an indirect and relatively slow report of neural activity, and underlying synaptic electrical and metabolic activity through neurovascular coupling is a topic of ongoing research and debate. As application of resting state functional connectivity measures is extended further into topics such as brain development, aging and disease, the importance of understanding the fundamental phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
157
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(179 citation statements)
references
References 65 publications
22
157
0
Order By: Relevance
“…Future studies using genetically-encoded neuronal calcium fluorescence reporters (i.e. GCaMP mice) or invasive electrophysiology [36][37][38][39] It is worth commenting on our choice of a mouse model. There are several mouse models of subarachnoid hemorrhage [40,41]; however, a perfect SAH model does not exist and there is not yet a consensus about which model to use for each experimental condition [42].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies using genetically-encoded neuronal calcium fluorescence reporters (i.e. GCaMP mice) or invasive electrophysiology [36][37][38][39] It is worth commenting on our choice of a mouse model. There are several mouse models of subarachnoid hemorrhage [40,41]; however, a perfect SAH model does not exist and there is not yet a consensus about which model to use for each experimental condition [42].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies recently addressed the contamination of the blood volume changes on fluorescence signal of calcium indicators like GCaMP (see, for instance, (Ma et al, 2016a;Ma et al, 2016b;Makino et al, 2017;Murphy et al, 2018;Wright et al, 2017)). The recent paper by Ma et al (Ma et al, 2016b) showed that the hemodynamic contribution is slower than the GCaMP6f signal, with an average temporal delay of 0.86 ± 0.05 s (representing the phase shift between neural activity and total hemoglobin concentration).…”
Section: Discussionmentioning
confidence: 99%
“…The recent paper by Ma et al (Ma et al, 2016b) showed that the hemodynamic contribution is slower than the GCaMP6f signal, with an average temporal delay of 0.86 ± 0.05 s (representing the phase shift between neural activity and total hemoglobin concentration). More recently, by simultaneously recording (wide-field) calcium dynamics and hemodynamics, Wright et al (Wright et al, 2017) showed that sensory evoked responses corresponding to oxygenated and deoxygenated hemoglobin have (i) a very slow onset after stimulus presentation, (ii) delayed peaks and (iii) low peak magnitudes (see also (Murphy et al, 2016)) compared to GCaMP6 fluorescence. These studies suggest that the hemodynamic fluctuations, much slower than calcium-associated neuronal activity, affect the late phase of calcium transients more than the rise.…”
Section: Discussionmentioning
confidence: 99%
“…The spectral content of the signals is analyzed to identify the frequency band which captures the spontaneous brain activity that occurs simultaneously with the motor-evoked events. Even though the slowest dynamics < 0.5 Hz , which has the highest power, is often a marker of the resting state (Wright et al, 2017), in this experiment it also contains the propagation of waves generated during the limb movements on the platform. The mechanisms behind stimulation propagation (Spiegler et al, 2016) are different from the spontaneous oscillations at rest (Deco and Jirsa, 2012) that we try to study and model here, and hence the lowest frequencies are excluded from the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the mice heart rate is between 6 − 8 Hz , whilst the activity above 10 Hz is too close to the Nyquist frequency of 12.5 Hz , defined as half of the sampling rate of the recordings. As a consequence these bands are generally avoided in the analysis of calcium signals, which is consequently often centered at the δ band between around 1 Hz and 5 Hz, (Vanni et al, 2017; Wright et al, 2017).…”
Section: Methodsmentioning
confidence: 99%